Analisis Kemampuan Makeup Artist Mengidentifikasi Kondisi Kulit Klien Ditinjau Dari Latar Belakang Pendidikannya - Sevia, Shafa Adrine; Ihsani, Ade Novi Nurul (Universitas Negeri Jakarta, 2024)
Makeup Artist is a profession that requires skill. The ability to apply makeup can be obtained through formal, non-formal, or informal education. A Makeup Artist must not only have the ability to apply makeup to clients but also to identify their skin conditions, which will affect the treatment that should be applied to each different skin condition. The purpose of this research is to analyze the ability of Makeup Artists with formal (university), non-formal, and informal education backgrounds to identify skin types. The research subjects were people who worked as Makeup Artists in Semarang with a minimum of 1 year of experience. Data collection techniques used in this research were interviews and questionnaires. Data analysis was performed using descriptive statistics. The research findings showed that out of the 45 MakeUp Artists with formal, nonformal, and informal education, the dominant level category was at the moderate level, with an average percentage above 60%. This indicates that the MakeUp Artists have fairly good abilities and are capable of identifying various skin conditions effectively. However, upon closer examination, there is a slight imbalance between the low and high levels. The analysis results demonstrated that MakeUp Artists with formal education have better theoretical, attitudinal, and practical skills in applying makeup for clients with different skin conditions. Informal education excelled in the affective and psychomotor skills. On the other hand, nonformal education showed significantly low percentages in both the affective and psychomotor abilities.